Aging sickness and death - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
In most modern cultures around the world, the goal is to stay young and sickness and death are often viewed as a personal failure. But some believe that in our culture that desperately seeks to avoid aging and death, we lose an opportunity for a growth.
Executive producer, Nasuhi Yurt
Host : MaryLynn Schiavi
DVD format
Keywords: Older people -- Health and hygiene; Older people -- Medical care